Value of Pollination by Honey Bees - Malcolm T. Sanford (EDIS)
This document is ENY-126, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: December 1992.